P3.062 Mycoplasma Genitalium Prevalence and Risk Factors Among Young Sexually Active Women in the General Population and Attending Sexually Transmitted Infection Clinics in London, UK. (13th July 2013) - Dave, S; Svenstrup, H; Carder, C; Grant, P; Morris-Jones, S; Kidd, I; Stephenson, J
Abstract : Background: Mycoplasma genitalium is a sexually transmitted infection (STI) associated with cervicitis, endometritis and pelvic inflammatory disease in women. There is a lack of data on M.genitalium in the United Kingdom. We conducted a study to determine its prevalence and risk factors among sexually active young women in the general population and attending STI clinics. Methods: First catch urine samples, self-taken vaginal and cervical swabs from 4644 women in the National Chlamydia Screening Programme (NCSP) and attending two London STI clinics were tested for M. genitalium by quantitative real-time PCR, confirmed by MgPa 1–3 genotyping. C.trachomatis results, demographic, sexual behaviour (NCSP only, 2470 women) and STI (clinics only, 2174 women) data were also available. Results: M. genitalium prevalence was 3%, C.trachomatis 5% and only 0.5% of women were co-infected. M.genitalium was more prevalent in swab than urine samples (4.6% vs. 1.4%, p < 0.001) with a significantly higher mean bacterial load. Among NCSP participants M.genitalium was associated with ethnicity (black 4.7% vs. white 2%, p = 0.01) and C.trachomatis with age (16–19 years 8.5% vs. 20–24 years 5.7%, p < 0.01). M.genitalium and C.trachomatis were detected more frequently in women reporting multiple sexual partners in the previous year compared to women who reported only one partner (OR 2.2, p = 0.02 and OR 1.8, p < 0.01, respectively). Among STI clinic attendees M.genitalium was associated with younger age (16–19 years 9.9%, 20–24 years 6.2% vs . > 25 years 1.7%, p = < 0.01). Chlamydia prevalence was 6% in STI clinic attendees aged 16–24. Women previously diagnosed with chlamydia or Trichomonas vaginalis were significantly more likely to have M.genitalium compared to women with no previous STI diagnoses (OR 2.4, p = 0.02 and OR 5.7, p < 0.01, respectively). Conclusion: M. genitalium and C. trachomatis seldom co-exist and appear to have different risk factors. Further data on M.genitalium are necessary to determine the need for routine testing and treatment.